How newly qualified primary teachers develop: A case study in rural Eritrea - Belay, Abraham; Ghebreab, Freweini; Ghebremichael, Tewolde; Ghebreselassie, Asmerom; Holmes, John; White, Goodith (International Journal of Educational Development, 2007)
This paper reports on the professional development of a small group of newly qualified teachers (NQTs) who began their careers in four rural schools in Eritrea. These teachers were monitored over a period of four years from 2001 to 2004. Their development as primary practitioners was recorded by videoing and observing their classes and by interviews and informal discussions held over the period. The ways in which they developed and the factors involved in this development are analysed and discussed. It is hoped that this research offers an insight into the challenges faced by newly qualified teachers in small rural communities, often very much dependant on their own resources and those of the local community. This indicates ways in which the current programme and on-going in-service provision may be targeted in future. An important point is made that in spite of the unusual circumstances of education in Eritrea this research provides insights that are relevant to other sociocultural contexts.
Keywords: African education; Educational quality; Rural education; Teacher development; __C:filed:1